Isomeric iodinated analogs of nimesulide: Synthesis, physicochemical characterization, cyclooxygenase-2 inhibitory activity, and transport across Caco-2 cells. Issue 16 (15th August 2016) - Yamamoto, Yumi; Arai, Jun; Hisa, Takuya; Saito, Yohei; Mukai, Takahiro; Ohshima, Takashi; Maeda, Minoru; Yamamoto, Fumihiko
Graphical abstract: Abstract: Isomeric iodinated derivatives of nimesulide, with an iodine substituent on the phenoxy ring, were prepared with the aim of identifying potential candidate compounds for the development of imaging agents targeting cyclooxygenase-2 (COX-2) in the brain. Both the experimental log P 7.4 and p K a values for these iodinated analogs were in the acceptable range for passive brain penetration. The para- iodo-substituted analog was a more potent and selective COX-2 inhibitor than nimesulide, with a potency that was comparable to the reference drug, celecoxib. Iodination at the ortho - or meta -position of the phenoxy ring was associated with a substantial loss of COX-2 inhibitory activity. Transport studies across Caco-2 cell monolayers in the presence and absence of a P-glycoprotein (P-gp) inhibitor, verapamil, indicated that the para- iodo-substituted analog was not a P-gp transport substrate; this feature is a prerequisite for potential in vivo brain imaging compounds. The para- iodo-substituted analog of nimesulide appears to be an attractive candidate for the development of radioiodine-labeled tracers for in vivo brain imaging of COX-2 levels.